1972
DOI: 10.1136/jnnp.35.2.149
|View full text |Cite
|
Sign up to set email alerts
|

Effects of hyperkalaemia on the excitability of peripheral nerve

Abstract: SUMMARY An experimental animal model has been developed for the study of excitability change in peripheral nerve during limb ischaemia. This model has been used to investigate the effects of hyperkalaemia on the sequence of excitability change that occurs during cuff-induced limb ischaemia and in the post-ischaemic recovery period. The results lend support to the hypothesis that the dynamics of K ion concentration in the periaxonal space play a critical role in determining these excitability changes and that t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
1

Year Published

1972
1972
1988
1988

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 14 publications
(4 citation statements)
references
References 20 publications
0
3
1
Order By: Relevance
“…Bischoff (1968) has observed that a significant thickening of the Schwann cell basement membrane was the earliest recognizable change in diabetic nerve. Seneviratne, Peiris, and Weerasuriya (1971) suggest that the resistance of diabetic nerve to inactivation by ischaemia may be due to an increase in the permeability of the muco-polysaccharide gap substance which occurs at the node of Ranvier, while the results reported in this study demonstrate an increased permeability of the 'tight junctions' between perineurial cells. These changes in the structure and properties of basement membranes of nonvascular structures draw attention to the likelihood that the diabetic process produces a more universal change in basement membrane function than has been hitherto recognized.…”
Section: Resultscontrasting
confidence: 52%
“…Bischoff (1968) has observed that a significant thickening of the Schwann cell basement membrane was the earliest recognizable change in diabetic nerve. Seneviratne, Peiris, and Weerasuriya (1971) suggest that the resistance of diabetic nerve to inactivation by ischaemia may be due to an increase in the permeability of the muco-polysaccharide gap substance which occurs at the node of Ranvier, while the results reported in this study demonstrate an increased permeability of the 'tight junctions' between perineurial cells. These changes in the structure and properties of basement membranes of nonvascular structures draw attention to the likelihood that the diabetic process produces a more universal change in basement membrane function than has been hitherto recognized.…”
Section: Resultscontrasting
confidence: 52%
“…A second line of evidence derives from the fact that the degree of resistance can be changed by experimental alterations of the periaxonal K' ion concentration. Seneviratne, Peiris, and Weerasuriya (1972) have shown that an increase in the serum K' ion concentration produces a significant reduction of the ischaemic inactivation time of cat peripheral nerve. Insulin increases the resting intra-axonal K' ion concentration, and nerves from healthy animals pretreated with insulin show an increased rate of K' efflux when they are exposed to anoxic conditions, leading to a local increase of the periaxonal K' ion concentration.…”
Section: Discussionmentioning
confidence: 99%
“…Seneviratne andPeiris (1969, 1970a) attribute this abnormality of the diabetic nerve to an increase in the permeability of its periaxonal diffusion barrier to K'. In a recent paper, Seneviratne, Peiris, and Weerasuriya (1972) have cited evidence which suggests that the polyanionic mucopolysaccharide gap substance which surrounds the bare axon at the node of Ranvier serves as the periaxonal diffusion barrier. The increased permeability of the diffusion barrier may be due to a reduction in the quantity of this gap substance at the node, or to a qualitative change in the nature of the mucopolysaccharide matrix which results in a reduction in its capacity to bind K' ions and hold them in close proximity to the axon at the node.…”
Section: Discussionmentioning
confidence: 99%
“…The critical role of the K' and the periaxonal diffusion barrier in determining the rate of change of excitability in ischaemic nerve in vivo has also been demonstrated. Seneviratne et al (1972) have shown that an acute increase in the serum K' level in the intact anaesthetized cat increases the excitability of its peripheral nerves. Cuff induced limb ischaemia leads to a more rapid inactivation of these nerves than in control cats, whereas release of the cuff leads to a slower rate of recovery.…”
mentioning
confidence: 99%